O sentido do sucesso: uma construção social made in USA - Ituassu, Cristiana Trindade (2012)
This paper investigates success as a social construction process based on an analysis of more than six hundred editions of Exame Magazine published over three decades. The proposed argument is that the concept of success is part of the culture of management that was introduced in Brazil together with administrative technologies, mainly in the 1950s. The herein adopted post-colonialist perspective allows for contextualizing the importation of management practices and principles that comprise managerialism, entrepreneurship culture and the cult of excellence. Throughout this process, we have highlighted the role played by the media in the dissemination, legitimization and coproduction of such mindset by describing the development of the concept of success in the United States and its reproduction in the Brazilian social imaginary. While pointing out the problems arisen from a definition of success connected to extrinsic and material aspects and recognizing that functionalist studies still have not been able to provide ways of expanding the term, we propose viewing success as an institution. Since language takes a central position in the social construction process, the empirical basis of this research is grounded on the discursive practices of the business media, given its role in the circulation of symbolic contents. The analysis on the editorials of the period from 1971 to 1998 uncovered three phases of the publication: one of self promotion; another one in which it legitimatized itself as a mouthpiece for businesses; and a third one, marked by personalization, when those responsible for the magazine appeared in all their personhood, thus reflecting a shift of its focus from organizations to individuals – a movement also made by the idea of success. The analysis on the reports showed that success gained prominence during the 1990s and allowed drawing a picture of the successful person according to Exame, namely an enterprising and ambitious man, white, slim and good-looking, mature in the 70s and young in the 90s, with a top position, high earnings and employability, but a troubled personal life. The analysis of the magazine covers strengthened this view. While we did not find any divergences in the definition of success throughout our analyses, we realized the valorization of the concept along with the meaning assigned to it in North America from the 1930s, which was more linked with the individual’s ability to impress than to the strength of his/her character. In the Brazilian context by the late twentieth century, success had to do with meeting job-related flexibility demands: each person is a business and needs to sell him/herself. The culture of management, clearly present in the analyzed publication, justifies this dynamics with a view of the world that reinforces the meaning of success with recognizably negative personal consequences. All this provides evidence that Brazil absorbed a made-in-the-USA success concept, as adopted and spread by Exame. Being attached to objective rewards, in face of so many possible interpretations, such institutionalized success was able to meet organizational interests by making up individualities committed to productive efforts. In the description of this dynamics lies our contribution towards the denaturalization of success, while inviting novel and alternative configurations for the term.